Halal and Biodegradable Food-Grade Grease from UMPSA makes its mark on the global stage - Mimi Rabita, Abd Wahit (UMPSA, 2025)
OSAKA, JAPAN, 21 July 2025 – A groundbreaking product developed through research at Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) has been selected to represent Malaysia at the prestigious World Expo Osaka 2025 in Japan.